Organisational behaviour - Moerdyk, A. P.; Dodd, Nicole; Donald, Fiona; Kiley, Jerome; Van Hoek, Gerhard; Van Hoek, Catharina Elizabeth (Oxford University Press Southern Africa, 2015)
"Organisational Behaviour is an introductory - level textbook which covers the basic theoretical foundations of individual, relationship and organisational behaviour. Current and up-to-date thinking is contextualised within management themes, including ethics, communication, negotiation and decision-making."--Resumé vydavatele
Keywords: organizační chování; management; organizational behavior; učebnice; textbooks